Capabilities for Complex Forensic Study of Objects of Phaleristics - G. G. Bocharov (Теория и практика судебной экспертизы, 2022)
The article addresses the methods used by traditional forensic examinations to study objects of phaleristics (orders and medals). The author justifies the necessity of a complex study of objects of phaleristics to ensure the completeness and validity of expert conclusions. Based on the examples from expert practice, the author also demonstrates the sequence of the actions of experts from different specialties in a complex investigation.Finally, the article provides the procedural characteristic of a comprehensive expert study.